HERMENEUTIKA MAKNA HIDUP DAN MATI PERSPEKTIF PENDIDIKAN AGAMA ISLAM DALAM TEMBANG GONDANG KELI GRUB KESENIAN RUKUN SARI KECAMATAN KERTEK - Faturrohman, Ahmad; Khoiri, Ahmad; Hanifah, Desty Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic Religious Education plays an important role in shaping human understanding of the meaning of life and death as decreed by Allah SWT. Such understanding is not only obtained through formal religious education, but can also be found in local cultural practices that live and develop within society. One form of local culture is the Gondang Keli chant, which is performed in the Topeng Lengger dance by the Rukun Sari Art Group in Kertek District. This study aims to explore the meaning of life and death in the Gondang Keli chant through a hermeneutic approach and to interpret it from the perspective of Islamic Religious Education. This research employs a descriptive qualitative method using observation, interviews, and textual analysis of the chant. The findings indicate that the Gondang Keli chant functions not only as entertainment, but also as a medium of spiritual messages and existential reflection on the transience of human life, as represented through symbols of water, crying, gentle musical rhythms, and trance phenomena during the performance. These meanings are in accordance with Islamic teachings on death, as stated in a hadith narrated by Muslim, which explains that a person’s deeds come to an end after death except for three: ongoing charity, beneficial knowledge, and the prayer of a righteous child.